A Prospective Assessment of an Adjustable, Immediate Fit, Transtibial Prosthesis. Issue 11 (1st April 2019) - Dillingham, Timothy; Kenia, Jessica; Shofer, Frances; Marschalek, Jim
Abstract : Background: There exists a need for an adjustable socket to accommodate residual limb volume and shape changes. Further, limb loss rates globally are rising and there is a large unmet need for affordable and accessible prosthetic systems. Objective: To assess the utility of an immediate fit modular prosthetic system (iFIT Prosthetics, LLC). Design: Prospective feasibility study involving a 2‐week single‐group pre‐post intervention study. Setting: Physical Medicine and Rehabilitation gait laboratory. Participants: Participants were at least 6 months post amputation and walking with a conventional prosthesis. They were free of skin wounds, other neurological disorders, and severe pain conditions. Methods: Participants were fit with an immediate fit prosthesis and instructed to wear it for a 2‐week evaluation period. They were given a progressive wearing schedule and they completed outcome measurements at the 2‐week follow‐up. Main Outcome Measurements: Self‐reported satisfaction, gait biomechanics, and intrasocket peak pressures. Results: Twenty‐six participants entered the study, with 22 completing the single group pre‐post study. They averaged 50 years (SD ±10.2) of age; four were female. Sixteen were dysvascular and 10 were traumatic in etiology. Significant differences ( P  = .03) in self‐reported satisfaction were found in favor of the iFIT device 29.33 (SD ± 4.51) versus the conventional device 25.52 (SD ± 6.8). No falls or limb ischemia were reported. Gait biomechanics revealed no differences across any temporal characteristics. Intrasocket peak pressures were significantly lower for the iFIT prostheses overall ( P  = .0014), at the anterior tibia ( P  = .0002), and the lateral side of the residual limb ( P  = .013). Conclusions: The iFIT transtibial prosthetic system appears to be safe in this short‐term single‐group pre‐post study. This study provided preliminary evidence to support the feasibility of the iFIT system. It compared favorably to participants' conventional prostheses across all outcome measures. With its cost, adjustability, and accessibility advantages, this device may prove useful for persons with transtibial amputations. A larger multicenter study is needed to confirm these results. Level of Evidence: III